2018
DOI: 10.1002/bit.26893
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an EGFR‐binding Gp2 domain for increased hydrophilicity

Abstract: The Gp2 domain is a 45 amino‐acid scaffold that has been evolved for specific, high‐affinity binding towards multiple targets and was proven useful in molecular imaging and biological antagonism. It was hypothesized that Gp2 may benefit from increased hydrophilicity for improved physiological distribution as well as for physicochemical robustness. We identified seven exposed hydrophobic sites for hydrophilic mutations and experimentally evaluated single mutants, which yielded six mutations that do not substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…One particular protein scaffold, Gp2, has been evolved into specific binding variants toward multiple targets (27)(28)(29). Continued study improved charge distribution (30), hydrophobicity (31), and stability (28). While these studies have suggested improvements for future framework and paratope residues (including a disulfide-stabilized loop), a poor developability distribution is still observed (32) (Fig.…”
mentioning
confidence: 99%
“…One particular protein scaffold, Gp2, has been evolved into specific binding variants toward multiple targets (27)(28)(29). Continued study improved charge distribution (30), hydrophobicity (31), and stability (28). While these studies have suggested improvements for future framework and paratope residues (including a disulfide-stabilized loop), a poor developability distribution is still observed (32) (Fig.…”
mentioning
confidence: 99%